Impact of disorder on optical phonons confined in CdS nano-crystallites embedded in a SiO2 matrix - Vasilevskiy, Mikhail (2001)
Non-resonant Raman spectroscopy studies of a set of CdS films annealed at different temperatures were performed and showed a direct correlation between the width of the Raman peak produced by CdS-like optical phonons and the crystalline quality of the semiconductor phase probed by x-ray diffraction (XRD) and transmission electron microscopy (TEM). In order to decribe the Raman lineshape a model proposed by Trallero-Giner et al (1998 Phys. Rev. B 57 4664) was used, which considers optical phonons confined in small semiconductor spheres with a size distribution. The model is shown to give a good reproduction of the spectra of samples where the semiconductor phase is most crystalline. However, it required too large values of phonon damping to fit the spectra of several other samples, which, according to XRD and TEM data, do contain CdS nano-crystallites. This large broadening of the Raman peak was considered as inhomogeneous, i.e. associated with disorder. Numerical lattice dynamics calculations were performed for 2D binary clusters of arbitrary shape and three kinds of disorder were considered, (i) random variation of the Cd–S bond frequency from one nano-crystallite to another, (ii) cluster shape irregularities and (iii) fluctuations of the nearest-neighbour interaction constant within one cluster. It is shown that ‘ensemble disorder’ (i) can be responsible for a shoulder above the bulk CdS phonon frequency observed for some of our samples. The effect of shape disorder (ii) is similar to that of the size dispersion producing some inhomogeneous broadening of the peak. In addition, it gives rise to an extra low-frequency mode originating from the top of the acoustic band. The force constant’s disorder (iii) is shown to result in a stronger asymmetric broadening of the Raman peak.